Listeria monocytogenes in raw salad vegetables sold at retail level in Malaysia. - Ponniah, Jeyaletchumi; Robin, Tunung; Paie, Margaret Selina; Radu, Son; Mohamad Ghazali, Farinazleen; Cheah, Yoke Kqueen; Nishibuchi, Mitsuaki; Nakaguchi, Yoshitsugu; Malakar, Pradeep Kumar (Elsevier, 2010)
A range of commercially available vegetables (n = 306) that are consumed in the minimally processed state in Malaysia was examined for the presence of Listeria spp. and Listeria monocytogenes to provide information on the occurrence of such organisms in these vegetables. Analysis was carried out using the most probable number–polymerase chain reaction (MPN–PCR) method. It was found that Listeria spp. and L. monocytogenes could be detected in 33.3% and 22.5% of the vegetables respectively. L. monocytogenes was more frequently detected in Vigna unguiculata (Japanese parsley) at 31.3% and Oenanther stolonifera (yardlong bean) at 27.2%.